Impact de la pollution sur les écosystèmes côtiers : exemple de la Manche orientale - Rachid Amara (VertigO)
Estuaries and coastal areas are high strategic areas for economies and environment. They perform many biological and ecological functions such as fish nursery grounds. The ecological functioning of these nurseries is vital to allow the normal life cycle of many marine species of major economic interests. In the Eastern English Channel the majority of fish species pass through these ecosystems during their life cycle. Yet there is an overlap between the main nursery areas and those subject to anthropogenic pressures. Comparative analysis of the quality of nursery areas has been addressed from a set of indicators of biological performance (fish growth and condition index) and chemical contamination (metal contaminants in fish tissue and sediment). Coastal areas strongly exposed to anthropogenic stressors (Seine estuary, coast between Calais and Dunkerque) provide lower quality habitat for fish development and survival. Many of the species that use coastal ecosystems are vital to the well-being of humans, either directly as a renewable resource value, or indirectly to maintain the functioning and sustainability of marine ecosystems. The need to protect these habitats from pollution and destruction is urgent.